Licorice Ingredients (IntechOpen, 2023)
Licorice extracts are used as additive to many Kampo medicines to alleviate pain and inflammation. With rapid progress of analytical methodology, its action mechanism is being elucidated. This book is composed of three sections. Section 1 introduces licorice as alternative medicine, its application in the industry, and the trading/market prospects between Japan and China. Section 2 summarizes the purification/identification steps of licorice ingredients and their antioxidant, antimicrobial, PPAR-? ligand-binding, antitumor, antiviral, and in vitro fertilization activities. Section 3 proposes the possible molecular mechanism by which licorice ingredients induce anti-inflammatory, antifibrosis, antihepatitis, and antileishmanial activity. All chapters are written by experts of natural sciences and economics and will surely give new insights into alternative medicines to students, clinicians, teachers, and researchers.